Generalized Hailey–Hailey disease: Novel splice‐site mutations of ATP2C1 gene in Chinese population and a literature review. Issue 2 (20th December 2020) - Yang, Lu; Zhang, Qianli; Zhang, Shiyu; Liu, Yuehua; Liu, Yaping; Wang, Tao
Abstract: Background: Hailey–Hailey disease (HHD; OMIM: 169600) is an autosomal dominate genodermatosis, characterized by recurrent blisters and erosions clinically and remarkable acantholysis pathologically. The underlying pathogenic factor is the mutation of ATP2C1 gene (OMIM: 604384), which encodes secretory pathway Ca 2+ /Mn 2+ ‐ATPase (SPCA1). Skin folds are the predilection site of HHD. Atypical cases with a generalized pattern have rarely been reported, making it prone to misdiagnosis. Methods: In this study, we presented three Chinese pedigrees of Hailey–Hailey disease with generalized skin lesions. ATP2C1 mutations were screened by DNA sequencing and their transcripts were further confirmed by minigene assay. We also performed a literature review of previously published generalized HHD over past two decades together with our cases. Results: Three splice‐site mutations were identified: c.2487+1G>A, c.2126+1G>A, and c.1891‐2A>G, which resulted in an exon 25‐truncated transcript, two exon 22‐truncated transcripts, and two exon 21‐truncated transcripts, respectively. The c.2487+1G>A and the c.1891‐2A>G mutations are novel mutations which have not been reported before. No clustered mutations of ATP2C1 gene were found in generalized HHD patients in literature along with our novel mutations. Conclusion: We found no hot spot mutations in ATP2C1 correlated with the generalized pattern of HHD. Our study expanded the spectrum of ATP2C1 mutations, which would be useful for disease diagnosis and genetic counseling. Abstract : The goal of our study was to explore the clinical and genetical features of generalized HHD. In our study, we identified three splice‐site mutations of ATP2C1 gene in three Chinese HHD pedigrees with generalized skin lesions, two of which have never been reported.